Analisis Pengaruh Ukuran Perusahaan, Konsentrasi Pasar, Cost to Income Ratio, Leverage, dan Diversifikasi terhadap Volatilitas Laba (Studi pada Bank Umum di Indonesia Periode 2009 - 2013) - Putra, Indra Eka; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2015)
Bank and risk couldnâ€™t be separated. Activities of the bank always contain risk for bank. Bank could take a higher risk to reach the bank earning desire. High risk-taking that bank took will impact to high bank earning volatility. Bank earning volatility will cause uncertainty of bank capital.Bank earning volatility in this study measured by standard deviation of ROA bank. This study used Fixed Effect Analysis Regression for panel data. The purpose of this study is to analyze the effect of firm size, market concentration, cost to income ratio, leverage, and divercification to bank earning volatility.Â The result of this study is firm size has positive effect and significant to bank earning volatility. Market Concentration has negative effect and significant to bank earning volatility. Cost to income has positive effect, but not significant significant to bank earning volatility. Leverage and divercification have negative effect but not significant significant to bank earning volatility.